Associations between cognitive function, actigraphybased and selfreported sleep in older communitydwelling adults: findings from The Irish Longitudinal Study on Ageing - Scarlett, Siobhan; Kenny, Rose (Wiley, 2020)
Objective: Cognitive impairment is prevalent in older ages. Associations with sleep are well established; however, ambiguity remains in which sleep characteristics contribute to this impairment. We examined cross-sectional associations between both self-reported and actigraphy-based sleep and cognitive performance across a number of domains in community-dwelling older adults. Methods: 1520 participants aged 50 and older with self-reported and actigraphy-based total sleep time (TST) (≤5, 6, 7-8, 9 and ≥10 h) and self-reported sleep problems were analysed. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), verbal fluency, immediate and delayed recall memory, colour trails tests, and choice reaction tests (CRT). Associations between sleep and cognition were modelled using linear and negative binomial regression. Results: Negative associations were found between ≥10 h of self-reported TST and MoCA error rate (incidence rate ratio [IRR] = 1.42; 95% confidence interval [CI] = 1.18, 1.71; p < 0.001); verbal fluency (beta [B] = -2.32 words; 95% CI = -4.00, -0.65; p < 0.01); and delayed recall (B = -0.91 words; 95% CI = -1.58, -0.25; p < 0.05) compared to 7-8 h. Significant associations with actigraphy-based TST were limited to MoCA error rate in ≤5 h (IRR = 1.22; 95% CI = 1.02, 1.45; p < 0.05) compared to 7-8 h. Higher numbers of sleep problems were associated with slower performance in CRT cognitive response time (IRR = 1.02; 95% CI = 1.00, 104; p < 0.05) and total response time (IRR = 1.02; 95% CI = 1.00, 1.04; p < 0.05). Conclusions: Self-reported long sleep duration was consistently associated with worse cognitive performance across multiple domains. Marginal associations between cognition and both actigraphy-based sleep and self-reported sleep problems were also apparent. These results further affirm poor sleep as a risk factor for cognitive impairment.
PUBLISHED
Keywords: Older population; Ageing; Actigraphy; Cognition; Accelerometer; Sleep; Cognitive impairment; Older adults; Ageing